Methodological construction of planning and management of sustainable urban development in Peru, assessment of sustainability in Lima Metropolitana - Chilet, Shirley (2017)
The conceptual and methodological contributlons of this research have been developed to recognize the importante that the cales have for a sustainable development. Thus, to resolve the problem, the social, environmental and economical aspects are analyzed and characterized in a Peruvian urban context, and the intermediate-size cales are analyzed particularly for a sustainable purpose. The topic of study goes through the evolutionary revision that it has had during the last decade the research, the management and the sustainable urban development evaluation in Latin America; just like the influence of the principal approaches in the employed models for the city's sustainability. The result analysis makes possible to confirm that guiding a sustainabledevelopment plan, it's necessary to build appropriate methodologies to know the urban reality of the cides In a sustainable context. The methodology plan that is presented includes research, management and the evaluatton,starting from a conceptual basis and the tools for each component. In the research; the sustainable development as a tool is proposed, and the basic guidelines are defined for a better connection with the different disciplines that are contained in, with the participation of all public and prívate representatives. For the management; politic sustainable acts and strategies for their implementation are proposed. For the evaluation a system where the componente, the dimensions, the phenomenon's and indicators are defined, is designed, which will allow to evaluate the condition in which the cides are in, and to know the rate or tendencyof urban sustainability. Asan integral pan of the methodological process of this research, the indicators are applied and the sustainability rate is estimated in the city of Lima, Peru. Finally, with the result of this research, an advance in conceptual and methodological construction is expected, to lead us into a sustainable study, in a complex system such as urban planning. Likewise, to contribute to conversations, discussions and the creation of consensus under a sustainable development premise in our country.